2016
DOI: 10.1136/gutjnl-2016-311849
|View full text |Cite
|
Sign up to set email alerts
|

RNF43 germline and somatic mutation in serrated neoplasia pathway and its association with BRAF mutation

Abstract: These results illustrate the importance of RNF43, along with BRAF mutation in the serrated neoplasia pathway (both the sporadic and familial forms), inform genetic diagnosis protocol and raise therapeutic opportunities through Wnt inhibition in different stages of evolution of serrated polyps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
176
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(193 citation statements)
references
References 79 publications
14
176
1
1
Order By: Relevance
“…This adds to two previous reports of germline mutations within RNF43 in individuals with SPS or who developed multiple serrated polyps 2 3. The current study by Yan et al 1 also importantly showed loss of second wildtype allele in 16 serrated polyps, five adenomatous polyps, and in the rectal adenocarcinoma from carriers through somatic single nucleotide variants or loss of heterozygosity, adding further weight to a potential role of RNF43 in the development of colonic serrated neoplasia.…”
supporting
confidence: 78%
See 2 more Smart Citations
“…This adds to two previous reports of germline mutations within RNF43 in individuals with SPS or who developed multiple serrated polyps 2 3. The current study by Yan et al 1 also importantly showed loss of second wildtype allele in 16 serrated polyps, five adenomatous polyps, and in the rectal adenocarcinoma from carriers through somatic single nucleotide variants or loss of heterozygosity, adding further weight to a potential role of RNF43 in the development of colonic serrated neoplasia.…”
supporting
confidence: 78%
“…The study by Yan et al 1 adds to the reported number of SPS families with germline mutations in RNF43 , now totalling four. The paucity of RNF43 germline LoF variants in 295 patients with SPS from the GCPS suggests that mutations in RNF43 may account for only a small proportion of SPS suggesting that additional genetic risk factors for SPS are yet to be identified.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…The high mutation rate suggests this mutations confers a positive selective advantage [13]. This was confirmed by Yan et al where biallelic RNF43 X659fs mutation, along with targeting of ZNRF3 , in a murine colon organoid model conferred R-spondin independence [27]. …”
Section: Discussionmentioning
confidence: 86%
“…For the top-down approach, additional alterations are added in the context of an established tumor. Many of these studies have analyzed the effects of particular genetic alterations observed in human tumors, such mutation of RNF43 or overexpression of miR-483 [81, 66]. Others have investigated particular genes of interest, such as PROX1 and BIM in the context of tumor cell survival and apoptosis resistance [82, 83].…”
Section: Modeling Cancer Biologymentioning
confidence: 99%